EXPLORING BOYCOTT MOVEMENTS AND RELIGIOUS AGRICULTURAL PRACTICES IN CONSUMER PURCHASING DECISIONS IN INDONESIA - Hanif Zafran Akbar; Hadi Peristiwo; Hendrieta Ferieka; Suryani Suryani; Efi syarifudin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The boycott movement has become an increasingly powerful social phenomenon in Indonesia, especially when linked to moral, political, and religious issues. This study aims to explore how boycott movements interact with religious agriculture in shaping consumer purchasing decisions, particularly for agricultural and food products. This study uses a mixed-methods approach with a convergent design, combining surveys to provide an overview of relationships among variables and in-depth interviews to understand consumer motivations and considerations better. The results show that participation in boycotts is influenced by ethical awareness, socio-religious solidarity, and exposure to information through social media. Meanwhile, agricultural religiosity reinforces preferences for halal, sustainable products that support local producers. These findings confirm that purchasing decisions are not only economic in nature but also reflect consumers' religious identities and moral attitudes.